Moderation and mediation analyses of exposure to television violence contents and contextual features and its influence on adolescents' aggressive behaviours / Mohammad Yaacob - Yaacob, Mohammad (2011)
Previous studies on the effects of exposure to television violence on viewers' aggressive behaviours have produced mixed results. Some studies have found significant effect sizes while others have found low and non-significant effect sizes. Television effects scholars have postulated that these mixed results are caused by the inconsistencies of research methodology employed and the inability to control major mediator variables in the studies. The present study is designed with the objectives to overcome these shortcomings. This study firstly validated and proposed measurement models for the variables and a full structural model for Television Violence Effects (TVE). Secondly, this study measured the influence of mediator and moderator variables on the relationship between exposure to Television Violence Contents (TVCN) and its effects on adolescents' aggressive behaviours. The respondents for this study were 514 students aged between 13 and 18 from 10 schools in the State of Perak. SPSS statistical software version 16 was utilized for preliminary data processing and AMOS version 5/16 was utilized for multivariate statistical data processing. The results provided evidence that the employed instruments achieved sound psychometric properties. All measurement models, TVE full structural model and all TVE nested path models achieved all standard model-fit indicators very well (Chi-Square/df < 3; GFI and AGFI > .09; and RMSEA < .05). Descriptive analyses of data showed that 53% of adolescents were exposed to television between three and four hours a day. Of 11 genres, adolescents ranked all television violence genres at number eight and above in their most favourite television programmes list. Hypotheses testing showed that exposure to TVCN did not have direct relationship with adolescents' aggressive behaviours; instead, Contextual Features of Television Violence (TVCX) totally mediated this relationship. Some other mediator variables then mediated totally and some mediated partially the relationship between TVCX and adolescents' aggressive behaviours. Hypotheses testing on the influence of moderator variables showed no significant differences in nested path models of TVE for different gender, place of residents, ethnic groups, levels of general television exposure and levels of academic achievements. To conclude, this study found that TVCX is the main factor beside other mediator factors such as adolescents' Television Viewing Self-Regulative Capabilities (SRGC), Personal Values (PV) and Aggressive Attitude (AGT) that determine the effects of exposure to television violence contents on adolescents' Aggressive Behaviours (AGB); regardless of their demographic backgrounds, the amount of television exposures and academic achievement levels. These findings are consistent with the predictions laid by theories guiding this study and with the findings from some previous studies. This study provides valuable information for parents, the television industry and the policy makers in recognizing pro-violent and anti-violent features of television violence programmes for Malaysian school adolescents. It also provides new perspective for future studies of television violence in Malaysia.